CENTRO HISTÓRICO DE DRACENA: IDENTIDADE E SALVAGUARDA - Luiza Sobhie Muñoz; Hélio Hirao (Universidade do Oeste Paulista, 2015)
This article is about the permanence of the initial landscapes in the historic center of Dracena identifying and mapping the set of significant architectural and urban planning, both historical and cultural elements that characterize its landscape. Dracena is a city of Presidente Prudente region, founded in 1945, located in the area known as New Alta Paulista, which arises due to the advancement of rails Company of Railroads. This research aims to observe the process of adulteration and dumping of these centers. It is argued, therefore, the function and significance of these historic centers in the daily life of the modern city to see how the people recognize and appropriate. The survey data allows these referrals subsidize shares for its preservation, preventing this important material memory of the city to lose support over time, strengthening local identity.